Unloading yield effect in a twin-roll-cast Mg–3Al–1Zn alloy. (15th April 2015) - Geng, J.; Nie, J.F.
Abstract : The yield point produced by unloading and reloading during tension was observed in a twin-roll-cast Mg–3Al–1Zn alloy. The magnitude of the unloading yield drop increased with increasing strain. Repeated stress relaxation tests were performed to quantitatively analyse the evolution of mobile dislocation density at 20 and 150 °C. The exhaustion rate of mobile dislocations at 20 °C is ∼11 times higher than that at 150 °C, and is considered to be responsible for the unloading yield effect at 20 °C.